2018
DOI: 10.1038/s41598-018-22615-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient Radiation Imaging Based on a ZnO:Ga Single-Crystal Image Converter

Abstract: A ZnO:Ga single crystal with an applicable size of φ40 × 1 mm was prepared using the hydro-thermal method. The crystal exhibits good crystallinity and scintillation properties with a 63.94-arcsec full-width at half-maximum (FWHM) in the X-ray rocking curve (XRC) spectrum, 8% luminous non-uniformity, emission at 389 nm in the X-ray excited luminescence spectrum, fast response and 5.5% BGO luminous intensity. Furthermore, an X-ray pinhole imaging system of nanosecond temporal resolution with a ZnO:Ga single-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…It is believed that such a scintillator with extremely fast decay time is of great importance in many research areas that require ultrafast scintillators. In addition, Xu [140] and Zhang [141] studied the application of ZnO:Ga scintillation crystals prepared by a hydrothermal method in pulsed radiation detection, as shown in Table 8. Table 8.…”
Section: The Application Research Status Of Zno:ga In Nuclear Detectionmentioning
confidence: 99%
“…It is believed that such a scintillator with extremely fast decay time is of great importance in many research areas that require ultrafast scintillators. In addition, Xu [140] and Zhang [141] studied the application of ZnO:Ga scintillation crystals prepared by a hydrothermal method in pulsed radiation detection, as shown in Table 8. Table 8.…”
Section: The Application Research Status Of Zno:ga In Nuclear Detectionmentioning
confidence: 99%
“…From Table 5, the FWHM of the as-grown GZO crystals is found to be 41.9 arcsec, which is lower than the currently reported values of GZO crystals. [22,37] The X-ray rocking curves imply that the as-grown GZO crystals have excellent lattice integrity. For the annealed samples, the GZO crystal orientation gradually deteriorates due to the increase of Ga-O and Zn-O bonds.…”
Section: Xrd Analysismentioning
confidence: 99%
“…ZnO has attracted much attention as a remarkable multi-functional material with a wide range of existing and emerging applications, such as varistors, , transparent conducting electrodes, surface-acoustic-wave (SAW) devices, , gas sensors, , X-ray imaging systems, and thin-film transistors. Several studies have reported that high-quality single-crystalline ZnO films grow on lattice-matched epitaxial substrates, such as bulk ZnO substrates and ScAlMgO 4 substrates. However, these substrates are expensive and thus make ZnO films of potentially limited use for large-scale devices. Cost-effective c -plane sapphire is a promising candidate as a substrate for the epitaxial growth of ZnO films because of its cost efficiency if single-crystalline ZnO films grew by overcoming the obstacle of the large lattice mismatch of 18%, which causes a number of crystal defects including 30°-rotated domains and threshold dislocations. , …”
Section: Introductionmentioning
confidence: 99%
“…ZnO has attracted much attention as a remarkable multifunctional material with a wide range of existing and emerging applications, such as varistors, 1,2 transparent conducting electrodes, 3−9 surface-acoustic-wave (SAW) devices, 10,11 gas sensors, 12,13 X-ray imaging systems, 14 and thin-film transistors. 15−19 Several studies have reported that high-quality single-crystalline ZnO films grow on lattice-matched epitaxial substrates, such as bulk ZnO substrates and ScAlMgO 4 substrates.…”
Section: ■ Introductionmentioning
confidence: 99%